Benchmarking Green Jobs Implementation in Tourism: Lessons from Global Best Practices for Indonesia - Prihatini, Rahma; Eddyono, Fauziah; Rusata, Tatang (Ilomata International Journal of Management, 2026)
The tourism industry plays a vital role in global economic growth while simultaneously exerting significant environmental pressures, including carbon emissions, waste generation, and ecosystem degradation. Addressing this duality, this study examines how green jobs can function as a strategic mechanism for enhancing tourism competitiveness through improvements in service quality, innovation, destination image, and compliance with sustainability standards, which collectively influence destination performance and visitor satisfaction. This research employs a qualitative descriptive approach based on a structured document analysis. A total of 68 policy documents, strategic plans, labor market reports, and certification frameworks (2015–2024) were analyzed across ten leading countries in the Travel & Tourism Development Index (TTDI) 2024—namely the United States, Spain, Japan, France, Austria, Germany, the United Kingdom, China, Italy, and Switzerland. Data were systematically coded using NVivo 15 to identify key themes related to policy frameworks, workforce development, certification systems, and institutional coordination. Cross-country comparison was conducted using a standardized thematic matrix to ensure analytical consistency.The findings indicate that advanced tourism economies have institutionalized green jobs through integrated governance structures, including national tourism strategies, certification schemes, and public–private partnerships that connect employment creation, digital transformation, and environmental management. In contrast, Indonesia’s current approach remains fragmented, with limited inter-ministerial coordination and insufficient integration of green competencies into vocational and higher-education systems.  The study contributes conceptually by proposing a Tourism Green Jobs Policy Readiness Framework, which integrates key dimensions of governance coordination, workforce development, certification systems, and financing mechanisms, and provides practical insights for Indonesia’s transition toward a sustainable, low-carbon tourism economy.